Efficacy and safety of certolizumab pegol for Crohn's disease in clinical practice. Issue 4 (17th June 2015) - Moon, W.; Pestana, L.; Becker, B.; Loftus, E. V.; Hanson, K. A.; Bruining, D. H.; Tremaine, W. J.; Kane, S. V.
Summary Background Certolizumab pegol (CZP) is Food and Drug Administration (FDA)‐approved to treat Crohn's disease (CD). However, the efficacy and safety of CZP outside clinical trials are not well established. Aim To report the efficacy, safety and predictors of response to CZP in CD patients treated during a 6‐year period since FDA‐approval at a tertiary care centre. Methods All CD patients who received CZP at our institution between 2008 and 2013 were evaluated through retrospective medical record‐based review of steroid‐free complete response (SCR), loss of response and safety. Results A total of 358 patients were included. One hundred twelve patients (31.3%) and 189 (52.8%) received CZP as their second and third biological agent, respectively. The probability of SCR at 26 week was 19.9% (95% CI, 15.9–24.5). The probability of survival free of loss of response at 2 year was 45.7% (95% CI, 32.5–59.5). A predictor of SCR was age at CD diagnosis of >40 years old (hazard ratio, HR relative to those <17, 4.69; 95% CI, 1.75–12.61). Negative predictors included present perianal fistula (HR, 0.39; 95% CI, 0.16–0.98) and prior primary nonresponse to adalimumab (ADA; HR relative to secondary loss of response, 0.18; 95% CI, 0.04–0.76). Twenty‐three patients (6.4%) experienced serious adverse events and 19 patients (5.3%) discontinued CZP due to adverse events. Conclusions Certolizumab pegol was both effective and well tolerated for the treatment of Crohn's disease in this large tertiary care centre enriched with biologics‐exposed patients. It may be more effective in patients without early‐aged Crohn's disease diagnosis, prior primary nonresponse to adalimumab and present perianal fistula.